Surfactants assisted solvothermal derived titania nanoparticles: synthesis and simulation - Dastan, Davoud; Chaure, Nandu; Kartha, Moses (Journal of materials science. Materials in electronics, 2017)
Solvothermal method was used to prepare titanium dioxide (TiO 2 ) nanoparticles (NP’s) of various morphologies at 180 °C growth temperature. Acetic acid and oley amine were used as surfactants. The powder of TiO 2 was annealed at 550 and 950 °C for 18 and 24 h. The influence of surfactants on the morphology of titania NP’s was investigated using transmission electron microscopy (TEM). The structural, optical, and molecular properties of titania NP’s are investigated by means of X-ray diffraction, UV–visible, Photoluminescence, and Fourier Transform Infrared. The physical properties, surface area and pore volume, of the samples were investigated by Brunauer-Emmett-Teller and Barrett-Joyner-Halenda measurement. The results illustrated type IV adsorption isotherms for all samples, implying the characteristics of mesoporous materials (2–50 nm). Furthermore, the hysteresis loops shifted to higher relative pressure, indicating that the specific surface area increases and the pore size decreases after heat treatment. Micrograph images acquired from TEM portrayed different shapes such as irregular spherical, rounded rectangular, truncated rhombic, and rod-like for titania NP’s when various surfactants were used. Monte-Carlo simulation carried out for pristine and rutile titania NP’s as representative samples explained the growth mechanism of titania NP’s and corroborated the formation of spherical and rod-like structures due to attractive and repulsive interactions among particle respectively.